Avaliação ecotoxicológica do hormônio 17α-metiltestosterona - Nogueira, Daniella Ventura (2019)
Within the pisciculture sector, for the cultivation of Nile Tilapia, some techniques have been developed to increase fish meat production. Among them, the masculinization of fingerlings, larval phase of tilapia, is an advantageous technique because the male is larger and produces more meat and having a monosexual population reduces the chance of overpopulation. For masculinization to occur, the hormone 17α-methyltestosterone (MT) has been used. It is administered by immersion baths containing the hormone or by adding it to the fish feed. Its use has raised concerns because, after its use, the effluents from the hormone-containing tanks are discharged untreated into water bodies reaching aquatic ecosystems and consequently humans through ingestion of contaminated water. Thus, the aim of this study was to evaluate the toxic effects of MT by ecotoxicological tests with acute and chronic tests with the organisms Daphnia magna, Scenedesmus acuminatus and genotoxicity with Allium cepa, using different trophic levels to determine the method that presents the lowest level of hormone toxicity. Acute and chronic MT assays were performed at concentrations of 10-100 µg L-1 and 750-1500 µg L-1 with Daphnia magna, which measured the immobility or lethality of organisms, and longevity and fecundity respectively. In the chronic assay with Scenedesmus acuminatus at concentrations of 750-1500 µg L-1, growth / inhibition of microalgae was evaluated. And in the genotoxicity and mutagenicity assay with Allium cepa at concentrations of 750 µg L-1 and 1500 µg L-1, the formation of chromosomal alterations, nuclear alterations and dividing cell micronuclei in onion root meristems was evaluated. Statistical analysis with Daphnia magna and Scenedesmus acuminatus was performed using Analysis of Variance (ANOVA) and treatment averages were compared using the Tukey test, with a significance level of 5% (α = 0.05). Allium cepa results were verified by the Kolmogorov-Smirnov test, comparisons were performed using one-way ANOVA and when there was a difference (p <0.05), the Dunnett test was applied. For acute toxicity tests with Daphnia magna, MT was not toxic at any of the tested concentrations, as well as for the chronic toxicity test, except for the appearance of resistance eggs (ephipians) at the highest concentrations, 1250 µg L -1 and 1500 µg L-1. For the chronic trial with Scenedesmus acuminatus, MT inhibited algal growth at the highest concentrations tested, being 1250 µg L-1 and 1500 µg L-1. In with onion the assay there was an increase in the formation of nuclear sprouts and micronuclei at a concentration of 750 µg L-1, and this difference was statistically significant. The results of this study showed that the 17α-methyltestosterone hormone has mutagenic and genotoxic action on onion and inhibition of growth of the tested microalgae, and may affect other organisms as well.